Housing for hope and wellbeing - Samuel, Flora (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"Housing and neighbourhoods have an important contribution to make to our wellbeing and our sense of our place in the world. This book, written for a lay audience (with policy makers firmly in mind) offers a useful and intelligible overview of our housing system and why it is in 'crisis' while acting as an important reminder of how housing contributes to social value, defined as community, health, self development and identity. It argues for a holistic digital map based planning system that allows for the sensitive balancing of social, environmental and economic value, the triple bottom line of sustainability, across our land mass and sets out a vision of what our housing system could look like if we really put the wellbeing of people and planet first, as well as a route map on how to get there. Written primarily from the point of view of an architect, the account weaves across industry, practice and academia cross cutting disciplines to provide an integrated view of the field. The book focuses on the UK housing scene but draws on and provides lessons for housing cultures across the globe. Illustrated throughout with case studies, this is the go-to book for anyone who wants to look at housing in a holistic way"--
Keywords: Housing -- Great Britain; Housing and health -- Great Britain; City planning -- Social aspects -- Great Britain; Well-being -- Great Britain; Community development -- Great Britain; ARCHITECTURE / General; ARCHITECTURE / Criticism; ARCHITECTURE / Domestic